Sistem Informasi Inventori Perusahaan Importir Buah Berbasis Web (Studi Kasus Ud. Numasari Buah) - Ni Made Santini; I Gede Putu Krisna Juliharta; J. Wahyu Nugroho Joshua (Primakara University, 2019)
There are several advantages of an inventory information system, including making it easier for companies to monitor the amount of stock of goods, making it easier for companies to produce reports or information for the benefit of the company, making it easier for companies to manage or market goods, minimizing. costs incurred due to human error and reduced working hours during the production process or ordering goods. Currently UD. Numasari Buah already has an inventory system that is still manual where inventory is carried out by manually counting the number of stock items in the warehouse one by one by writing on notebook paper or log book. So from that the authors want to create a web-based inventory information system that earmarked for UD. Numasari Buah to make it easier to do work in inventory at the company so that it becomes more efficient. So from the case above the author came up with the title